Preventive Deradicalization in Lower Grade Madrasah through Religious Moderation in Quran-Hadith and Aqidah-Akhlak - Bachtiyar, Machfud; Zaini, Abdullah; Pangastuti, Ratna (STAI Miftahul Ula Nganjuk, 2024)
This study investigates preventive deradicalization efforts in lower-grade students of Madrasah Ibtidaiyah through the internalization of religious moderation values in Quran-Hadith and Aqidah-Akhlak subjects. Utilizing a qualitative descriptive approach, the research subjects were selected purposively, and data were gathered via in-depth interviews, participatory observation, and documentation. The analysis followed Miles, Huberman, and Saldana's interactive model, involving data condensation, presentation, and conclusion drawing, with data validity ensured through credibility tests and triangulation. The findings indicate that nationalistic values were instilled in students through value transformation by teachers, value transaction in flag ceremonies, and transinternalization, where students memorized the national anthem and Pancasila principles.